Post-treatment evaluation of combined odontogenic keratocyst and ameloblastoma using fractal dimension analysis: Evaluasi pascaperawatan kombinasi odontogenic keratocyst dan ameloblastoma menggunakan analisis fraktal dimensi - Uce Ayuandyka M; Rezky Amalia; Donna Trye Liling; Virdha Dwi Mulya; Barunawaty Yunus (Makassar Dental Journal, 2026)
Odontogenic keratocyst (OKC) and ameloblastoma are common odontogenic lesions, often occurring in the posterior part of the mandible. Panoramic radiogra-phic examination with fractal analysis has been proven very effective in evaluating trabecular bone and assessing disease prognosis by comparing preopera-tive and postoperative images of the lesion. This article evaluates the combined treatment of OKC and ameloblastoma through the application of fractal analy-sis on panoramic radiographs. A 20-year-old female presented with a complaint of swelling in the left mandible that had been ongoing for about three months. Objective examination showed facial asymmetry marked by enlargement of the posterior mandible. Radiographic examination showed multiple irregular ra-diolucent lesions resembling soap bubbles. The case was diagnosed as a combination of OKC and ameloblastoma. It is concluded that the dredging method has been proven effective in the treatment of OKC and ameloblastoma. Fractal analysis calculations have been proven to be very useful in the field of den-tistry for disease monitoring purposes.